2007
DOI: 10.1074/jbc.m701752200
|View full text |Cite
|
Sign up to set email alerts
|

ZnT5 Variant B Is a Bidirectional Zinc Transporter and Mediates Zinc Uptake in Human Intestinal Caco-2 Cells

Abstract: Zinc is an essential micronutrient, so it is important to elucidate the molecular mechanisms of zinc homeostasis, including the functional properties of zinc transporters. Mammalian zinc transporters are classified in two major families: the SLC30 (ZnT) family and the SLC39 family. The prevailing view is that SLC30 family transporters function to reduce cytosolic zinc concentration, either through efflux across the plasma membrane or through sequestration in intracellular compartments, and that SLC39 family tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 19 publications
1
78
1
Order By: Relevance
“…Human ZnT5 has one splice variant, ZnT5B (hZTL1), that has quite different characteristics from hZnT5 (38,39). ZnT5B (hZTL1) is localized to the plasma membrane and functions to enable zinc uptake from the extracellular environment -the opposite direction of zinc transport by hZnT5/hZnT6 heterodimers.…”
Section: Discussionmentioning
confidence: 99%
“…Human ZnT5 has one splice variant, ZnT5B (hZTL1), that has quite different characteristics from hZnT5 (38,39). ZnT5B (hZTL1) is localized to the plasma membrane and functions to enable zinc uptake from the extracellular environment -the opposite direction of zinc transport by hZnT5/hZnT6 heterodimers.…”
Section: Discussionmentioning
confidence: 99%
“…Among the most striking are decreased bone density, reduced weight, and fatal, male-specific, cardiac bradyarrhythmia (9). ZnT5 has been also shown to mediate Zn 2ϩ uptake (10). It has also been suggested that ZnT5 subunits assemble with those of ZnT6 and that this hetero-oligomerization is required for the activation of the Zn 2ϩ -dependent alkaline phosphatases (11).…”
Section: Znmentioning
confidence: 99%
“…Mammalian Zn transporters play a key role in the tight regulation of Zn homeostasis (18) and are classified into two metal-transporter families, ZRT or IRT-like proteins (ZIP transporters; classified as solute carrier family SLC39) and the cation diffusion facilitators (ZnT transporters; classified as solute carrier family SLC30). Members of the SLC39 family have been found to promote influx of Zn into the cytosol of the cell, whereas those of the SLC30 family reduce cytosolic Zn concentration by either Zn efflux from the cell or the sequestration of Zn into intracellular compartments (25) . To date, a number of human Zn transporters have been characterised.…”
Section: Zinc Absorptionmentioning
confidence: 99%
“…The human splice variant, ZnT5 variant B, acts as a bidirectional Zn transporter when expressed in Xenopus laevis oocytes, i.e. it is active in both the uptake and efflux of Zn (25) . The bidirectional function of ZnT5 suggests a possible role in dietary Zn absorption.…”
Section: Zinc Absorptionmentioning
confidence: 99%